Socio-environmental adaptations in a new low-cost housing estate / Wong Mok Lan - Wong , Mok Lan (1981)
This academic exercise is a study of the residents’ early stages of socio-environmental adaptations to the Rancangan Rumah Rakyat Dusun Nyior 2a housing estate. A total of 30 households, 15 Malay and 15 Chinese were selected from 95 units for study. The first chapters generally discusses the low-cost housing situation in Malaysia and some socio-psychological aspects of housing. Chapter two includes the presentation of the purpose of study and a review of related literatures. In chapter three, the author explains the method of sample selection and design adopted for the study. The findings of the research are analyse and discussed in the following chapter. In the final chapter, conclusions are drawn from the findings and a few suggestions are offered for the possible solution of certain problems.